Cultural promotion of Peranakan Baba Nyonya through visual information - Mah, Phui Yan (Universiti Malaysia Sarawak (UNIMAS), 2012)
Peranakan Baba Nyonya is a unique ethnic group which combining two cultures, the Chinese and Malay. The heritage of Peranakan Baba Nyonya has published many articles and documentation in writings. This study will highlight the cultural promotions in a form of visual communication which emphasizes the visual design and history for preservation.